2008
DOI: 10.1063/1.2957667
|View full text |Cite
|
Sign up to set email alerts
|

Barrier effect on hole transport and carrier distribution in InGaN∕GaN multiple quantum well visible light-emitting diodes

Abstract: Carrier distributions governed by hole transport in InGaN∕GaN multiple quantum well (MQW) visible light-emitting diodes (LEDs) were investigated using conventional blue LEDs and dual-wavelength blue-green LEDs. It was found that holes were dominantly distributed in the QW close to the p-GaN layer in LEDs with conventional MQW active regions at a current of 20mA. A decrease in the thickness or the height of the quantum-well potential barrier enhanced hole injection into the MQWs located near the n-GaN layer. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 10 publications
5
88
0
Order By: Relevance
“…Since CL gives a measure of R R and EBIC directly measures I EBIC , an indirect measure of relative nonradiative recombination is made possible by simultaneous measurement of CL and EBIC. Carrier recombination and transport in LEDs are also strongly influenced by the applied electric field, both across the whole depletion region in the form of carrier overshoot and capture [10][11][12][13] and also in the quantum wells themselves via tunneling 13,14 and the quantum-confined Stark effect (QCSE). 15 Consequently, the applied voltage greatly affects the intensity and spectral characteristics of the CL spectrum as well as the EBIC.…”
Section: Introductionmentioning
confidence: 99%
“…Since CL gives a measure of R R and EBIC directly measures I EBIC , an indirect measure of relative nonradiative recombination is made possible by simultaneous measurement of CL and EBIC. Carrier recombination and transport in LEDs are also strongly influenced by the applied electric field, both across the whole depletion region in the form of carrier overshoot and capture [10][11][12][13] and also in the quantum wells themselves via tunneling 13,14 and the quantum-confined Stark effect (QCSE). 15 Consequently, the applied voltage greatly affects the intensity and spectral characteristics of the CL spectrum as well as the EBIC.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental information about carrier distributions can be obtained from quantum well structures with different indium content in each of the InGaN quantum wells: each well then emits its own characteristic color. [3][4][5][6][7] In this way one can also monitor how a carrier distribution evolves with increasing bias current. The factors that determine the carrier transport between quantum wells are the effective mass of the carriers, and the height and thickness of the barriers, both in the conduction band and in the valence band.…”
mentioning
confidence: 99%
“…Figure 3 illustrates this behavior as observed for the case of the "2+1" LED. We believe that this is because holes are injected into the active region and recombine predominantly in the QW close to the p-GaN layer [3][4][5]. We found that electroluminescence intensity produced by "1" LED, "1+1" LED, and "2+1" LED gives a ratio of intensities corresponding roughly to 1:7:2, respectively.…”
Section: Resultsmentioning
confidence: 76%